058 Pre-surgical evaluation in focal cortical dysplasia: a role for EEG-fMRI?. Issue 3 (9th February 2012) - Thornton, R; Vulliemoz, S; Rodionov, R; Carmichael, D W; Chaudhary, U J; McEvoy, A W; Diehl, B; Walker, M C; Guye, M; Bartolomei, F; Duncan, J S; Lemieux, L
Abstract : Background: Epilepsy surgery in patients with Focal cortical dysplasia (FCD) is most successful if all epileptogenic tissue is resected. This may not be evident on structural MRI so intracranial EEG (icEEG) is often required to delineate the seizure onset zone (SOZ). EEG-fMRI can reveal interictal discharge (IED) related haemodynamic changes, concordant with the irritative zone (IZ) and SOZ. We present the first systematic comparison of EEG-fMRI with icEEG and post-operative outcome in patients with FCD and focal epilepsy. Method: 23 patients with FCD-associated epilepsy undergoing presurgical evaluation including icEEG underwent EEG-fMRI at 3 Tesla. Maps of IED-related haemodynamic change were overlaid on co-registered T1-weighted MRI scans fused with CT scans following implantation of intracranial electrodes and compared with icEEG and post-operative outcome at 1 year. Results: 12/23 patients had IEDs during recording and IED-related haemodynamic changes were seen in 11/12. Results concordant with the SOZ±IZ were revealed in 6/12 patients. 5/6 underwent resection with >50% reduction in seizure frequency. 5/12 patients had widespread regions of IED-related BOLD signal change and 4/5 had a diffuse/multi-focal SOZ on icEEG precluding successful resective surgery. Conclusion: EEG-fMRI provides useful information about the SOZ in FCD. Widespread discordant regions of IED-related BOLD signal change are associated with a multifocal/diffuse SOZ on icEEG and poorer surgical outcome.